Pengaruh Dana Perimbangan, PDRB per Kapita, Tax Effort, dan Jumlah Penduduk terhadap Pendapatan Asli Daerah (Studi Kasus Kabupaten/Kota Provinsi Jawa Tengah Tahun 2011-2017) - Noor Fikri Muhammad (Universitas Diponegoro, 2021)
Since the era of Fiscal Decentralization, the role of Local Revenue in Central Java Province has not been seen. This can be seen from the portion of Local Revenue which is quite small compared to the Balancing Fund in the total regional revenue. This raises the suspicion that the Regional Government will depend on the Balancing Fund. But in this study also looked at the influence of other variables that might be able to influence the acceptance of Local Original Revenues, among others, Per Capita GRDP, Tax Effort, and Population Amount. The purpose of this study was to determine whether the variable Balancing Funds, Per Capita GRDP, Tax Effort, and Population affect the acceptance of Local Original Revenue. This study uses secondary data with cross section panel data of 35 districts / cities in Central Java and a 7-year time series from 2011-2017. The analytical tool used in estimating this research model is panel data regression using the newey-west method. The results of this study indicate that the variable Balance Funds, Per Capita GRDP, and Tax Effort. has a positive and significant influence on Local Revenue in the province of Central Java in the period 2011-2017. While the Population has no influence on Local Revenue in the province of Central Java in the period 2011-2017.